EFEKTIFITAS PEMBELAJARAN E-LEARNING PADA MASA PANDEMI COVID 19 TERHADAP MOTIVASI BELAJAR MAHASISWA - Lutfi Wahyuni; Rudi Hariyono; Agus Haryanto (Nurse and Health: Jurnal Keperawatan, 2021)
Background: This pandemic has caused many changes in various aspects of life including education. This change happened so fast and did not allow us to make preparations and anticipation so that the impact would not be so great. Learning at this time is more directed at modernization activities with the help of advanced technology with the hope of helping students digest lecture material in an interactive, productive, effective, inspirational, constructive, and fun way. Objective: The aim of the research was to prove the effectiveness of e-learning during the Covid-19 pandemic on the learning motivation of students in the Nursing Study Program at STIKES Bina Sehat PPNI Mojokerto. Methods: The research design used in this research is comparative exploratory which is used to describe and mention the differences and similarities of the subject under study. The sampling technique in this study used simple random sampling approach. The sample in this study was partly students in semester 6, with a sample size of 120 respondents. Collecting data using a questionnaire. This questionnaire is a modification of the previous questionnaire from Nursalam (2016) with a likert scale distributed by google form. Results: Based on the data on the effectiveness of E-Learning, most of the respondents answered that it was quite effective as many as 79 respondents or 66%, while the motivation of the students was mostly less motivated in learning as many as 89 respondents or 75%. Spearman Rho Statistical Test are obtained ? = 0.000 with the Correlation Coefficient (r) = 0.318 which indicates a weak relationship. Conclusion: The presence of online learning methods (E-Learning) makes students motivated to learn again. During this pandemic period, it is hoped that students will remain motivated to learn and continue to attend lectures through E-Learning with various media.